2015 IEEE 9th International Conference on Intelligent Systems and Control (ISCO) 2015
DOI: 10.1109/isco.2015.7282275
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalogram based diagnosis of Alzheimer Disease

Abstract: Alzheimer Disease is one of the most common & tremendously growing neurological diseases in the world. Several biomarkers tools exist for diagnosis & disease progression in Alzheimer disease which can be assumed as key issues for clinical applications. Electroencephalogram signals (EEG) yields out powerful and relatively cheap tool of diagnosis of different neurological disease. The need in this case is to improve the diagnostic accuracy of the EEG signals. In this paper, a new methodology for diagnosis of Alz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…The use of electroencephalography (EEG) has recently grown as a means to diagnose neurodegenerative pathologies such as AD [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. EEG is a non-invasive test that records the electrical activity of the brain measured at different sites on patient’s scalp, resulting in indirect information about the physiological conditions of the brain.…”
Section: Introductionmentioning
confidence: 99%
“…The use of electroencephalography (EEG) has recently grown as a means to diagnose neurodegenerative pathologies such as AD [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. EEG is a non-invasive test that records the electrical activity of the brain measured at different sites on patient’s scalp, resulting in indirect information about the physiological conditions of the brain.…”
Section: Introductionmentioning
confidence: 99%
“…EEG straightforwardly relates the brain activity which is used for observing the various function of brain. Different neurological disease is diagnosed based on the significant features computed from the various non-linear and linear analyses of sampled EEG Signals [10]. Different methods for diagnosing the AD are compared in the table I and literature summary for the detection of AD based on EEG signals summarized in the table II.…”
Section: Methodsmentioning
confidence: 99%
“…The bioelectric cells are non-invasively examined by series of electrodes placed over patients head as per international 10/20 standards. EEG signal is simply a multivariate signal transmitted over different channels with variation of different sampling frequencies depending on each application [4,5]. This tool takes more time as it generates more data which needs to be analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…EEG signals are key diagnostic tools not only for neurologists, but also for clinicians and doctors. Today, EEG recordings are also used in many Brain Computer Interface (BCI) applications [4]. Several research findings have identified the potential of EEG for diagnosing dementia and Alzheimer's disease in recent years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation